Low-molecular Weight Heparin Reduces the Generation and Activity of Thrombin in Unstable Coronary Artery Disease - Ernofsson, Mats; Strekerud, Finn; Toss, Henrik; Abildgaard, Ulrich; Wallentin, Lars; Siegbahn, Agneta (Thrombosis and Haemostasis, 1998)
Unstable coronary artery disease (UCAD) is associated with an increased risk of further coronary events. In the FRISC study, the risk was decreased during treatment with a high, twice-daily, dose of dalteparin, a low-molecular-weight heparin. However, lowering the dose resulted in raised risk of recurrences. To investigate the underlying pathophysiology, the thrombin generation and activity in patients with UCAD randomized to a 6-week placebo-controlled treatment with dalteparin were evaluated.Plasma prothrombin fragment 1+2 (F1+2) (n = 342), thrombin-antithrombin complex (TAT) (n = 186) and soluble fibrin (SF) (n = 298) were analyzed before and during treatment with dalteparin/placebo administered subcutaneously, 120 IU/kg bw twice daily for 5-8 days and 7,500 IU once daily the following 35-40 days. High-dose treatment with dalteparin resulted in significantly reduced levels of all coagulation markers, demonstrating diminished thrombin generation and activity. When reducing the dalteparin dose, plasma TAT and SF remained low, indicating minimal fibrin formation. However, F1+2 increased during this period, though the level at day 45 was still lower than in the placebo group. In the placebo group elevated thrombin generation and activity persisted during the entire period.In conclusion, high-dose treatment with dalteparin twice daily resulted in significantly reduced thrombin generation and activity. However, after changing to a lower, once-daily dose, the treatment was not sufficient in preventing a return to a procoagulable state. These changes of the coagulation activity might explain the changes in event rate observed during dalteparin treatment.